Assessing the Use of Standardized Outcome Measures for Stroke Rehabilitation among Physiotherapists in Ghana - Seth Kwame Agyenkwa; Cosmos Yarfi; Adjoa Nkrumah Banson; Woyram Abla Kofi-Bediako; Ulric Sena Abonie; Seth Kwadjo Angmorterh; Eric Kwasi Ofori (Stroke Research and Treatment)
Background. The use of standardized outcome measures is an aspect of good clinical practice and essential to the rehabilitation of patients suffering from stroke. Literature reports regarding the extent of usage of outcome measures in stroke rehabilitation by physiotherapists globally are inconsistent. In addition, the patronage of outcome measures in stroke rehabilitation in low-resourced countries is uncertain. Objective. This study was conducted to assess the current practice of physiotherapists in Ghana regarding the use of standardized outcome measures in the rehabilitation of stroke patients. Method. A descriptive cross-sectional survey, was used involving 105 registered physiotherapists in Ghana. A 35-item adapted questionnaire was used to collect data on some commonly used outcome measures and frequency of use by physiotherapists for stroke patients. Results. A total of 55 (52.4%) physiotherapists did not use outcome measures in their clinical practice. Physiotherapists below 40 years of age use outcome measures (64.7%) more than those 41 years and above (6.7%). Physiotherapists working in public facilities in Ghana are more likely to use outcome measures (56.2%) than those in private facilities (16.2%). Physiotherapists who attend to 1-10 patients in a week used outcome measures more (32.4%) than physiotherapists who attend to more than 30 patients (3.8%) in a week. Conclusion. There is poor usage of outcome measures by Ghanaian physiotherapists, with more than half of the participants not using any standardized outcome measures for rehabilitation of patients in their practice. Physiotherapists who attends to fewer number of patients in a week are more likely to use outcome measures. There is the need for implementation of policy and guidelines on the use of outcome measures by the Allied Health Professions Council and the Ghana Physiotherapy Association.